Care full : medico-legal reports and the Istanbul Protocol in asylum procedures - Bruin, René; Reneman, Marcelle; Bloemen, Evert (Utrecht: Pharos, 2006)
"edted by René Bruin, Marcelle Reneman, Evert bloemen"